Divide Precisely and Proliferate Safely: Lessons From Budding Yeast - Fraschini, Roberta (Frontiers in Genetics, 2019)
.A faithful cell division is essential for proper cellular proliferation of all eukaryotic cells; indeed the correct segregation of the genetic material allows daughter cells to proceed into the cell cycle safely. Conversely, errors during chromosome partition generate aneuploid cells that have been associated to several human pathological conditions, including cancer. Given the importance of this issue, all the steps that lead to cell separation are finely regulated. The budding yeast Saccharomyces cerevisiae is a unicellular eukaryotic organism that divides asymmetrically and it is a suitable model system to study the regulation of cell division. Humans and budding yeast are distant 1 billion years of evolution, nonetheless several essential pathways, proteins and cellular structures are conserved. Among these, the mitotic spindle is a key player in chromosome segregation and its correct morphogenesis and functioning is essential for genomic stability. In this review we will focus on molecular pathways and proteins involved in the control mitotic spindle morphogenesis and function that are conserved from yeast to humans and whose impairment is connected with the development of human diseases.